Synthesis and Pharmacological Evaluation of (+)-Usnic Acid Derivatives as Hypoglycemic Agents - Sergey A. Borisov; Olga A. Luzina; Mikhail V. Khvostov; Tatiana G. Tolstikova; Nariman F. Salakhutdinov (Molbank, 2022)
Usnic acid is produced by lichens and exhibits different biological properties, including hypoglycemic ones. However, this effect becomes noticeable only at relatively high doses, something that may lead to some adverse effects. The chemical modification of the molecule is able to enhance its safety profile and its hypoglycemic properties. We synthesized six enamine derivatives of (+)-usnic acid, and two of them are novel. All compounds were evaluated for the hypoglycemic effect after oral introduction in mice with alloxan-induced diabetes mellitus at a dose of 50 mg/kg. The derivative containing a 4-trifluoromethylphenyl fragment showed the most pronounced hypoglycemic effect, which was detected starting from sixth day of the experiment. Also, OGTT was performed in mice without alteration of glucose metabolism (C57BL/6), which showed no hypoglycemic effect after oral introduction of all studied compounds.